Impact of prenatal diagnosis on the outcome of patients with a transposition of great arteries: A 24‐year population‐based study. Issue 3 (21st December 2015) - Debost‐Legrand, Anne; Ouchchane, Lemlih; Francannet, Christine; Goumy, Carole; Perthus, Isabelle; Beaufrère, Anne‐Marie; Gallot, Denis; Lemery, Didier; Lusson, Jean‐René; Laurichesse‐Delmas, Hélène
Abstract : Background: Transposition of great arteries (TGA) defined as the combination of concordant atrioventricular and discordant ventriculo‐arterial connections is one of the most common congenital heart defects. Prenatal diagnosis of TGA remains difficult. To determine the impact of antenatal diagnosis we evaluated the sensitivity of antenatal detection and the neonatal mortality of TGA considering two study periods and two major types of TGA. Methods: A cross‐sectional study was performed. Data were collected from a French population‐based birth defect registry. From 1988 to 2012, 94 fetuses with TGA were registered. The study period was subdivided into the 1988 to 1999 period and the 2000 to 2012 period. Two types of TGA were considered: isolated TGA ( n = 66) and associated TGA ( n = 28). A stratified analysis was performed considering the study periods and the types of TGA. RESULTS: Considering the study periods, the sensitivity of prenatal detection of TGA increased significantly (9.8% vs. 51.5%, p = 0.0001). The same trend was found for associated TGA (4.8% vs. 33.3%, p = 0.002) and isolated TGA (21.1% vs. 100%, p < 0.001). A late diagnosis of TGA (7 days after birth) was observed in 13.2% of cases. Neonatal mortality decreased significantly over time for isolated TGA (25.0% vs. 0 p = 0.01). Prenatal diagnosis of both types of TGA did not improve survival. Conclusion: We demonstrated that prenatal diagnosis and neonatal mortality of TGA varied greatly according to the malformation type and the study period. This could be explained by an improvement in terms of medical management. Birth Defects Research (Part A) 106:178–184, 2016. © 2015 Wiley Periodicals, Inc.